Significance of multiple neurophysiological measures in patients with chronic disorders of consciousness. Issue 3 (March 2015) - Rossi Sebastiano, Davide; Panzica, F.; Visani, E.; Rotondi, F.; Scaioli, V.; Leonardi, M.; Sattin, D.; D'Incerti, L.; Parati, E.; Ferini Strambi, Luigi; Franceschetti, S.
Highlights Preservation of spatially distributed EEG alpha characterises patients in an MCS. The maintenance of variable sleep patterns is a strong indicator of the severity of the disorder of consciousness (DOC). The combination of EP and EEG patterns helps to classify chronic DOCs.